Re-Dimensioning the Polish-German Border Area: Poznań as a City in a Transnational Cooperation Space - Tölle, Alexander (Quaestiones Geographicae, 2010)
The declining importance of national policies and the economic level as a result of globalisation as well as European integration processes compels cities to become actors on the international stage and to define their own ‘foreign policies’, which may include the establishment of transnational alliances, networks, and cooperation territories. This will be discussed using Poznań as a case study. After the fall of the Iron Curtain the city had to integrate into traditional forms of international cooperation as well as new forms of transnational networking. Concerning the latter, the biggest challenge is the integration of Poznań into the strategic network of the Oder Partnership, which aims at creating a Polish-German cooperation space able to compete with other European regions.